The effect of induction of labour on perinatal mortality and obstetric outcomes: a population database study. (16th November 2010) - Stock, SJ; Ferguson, E; Duffy, A; Ford, I; Chalmers, J; Norman, JE
Abstract : Background: Induction of labour (IOL) >41 weeks decreases perinatal mortality without increasing Caesarean rates.1 However, there is lack of data regarding outcomes of IOL prior to 41 weeks, particularly regarding effects on perinatal mortality. Aim: To determine outcomes associated with IOL at term compared to expectant management. Methods: Interrogation of an unselected population database of 1.6 million births in Scotland (SMR02/SMR11/SBR/SSBID/GROS) between 1981 and 2007. Outcomes of women who underwent medically indicated or 'elective' (no recognised medical indication) IOL at 37-, 38-, 39-, 40- and 41-week gestation were compared to those of women who were managed expectantly (continued the pregnancy to either labour spontaneously or have IOL or Caesarean delivery at a later gestation). Women with contraindications to IOL were excluded. Multivariate analysis adjusted for age, year, parity and deprivation category. Results: Elective IOL was associated with decreased perinatal mortality when compared to expectant management (adjusted OR (AOR) 0.14 (0.04–0.43) at 37 weeks increasing to 0.32 (0.23–0.45) at 41 weeks). Odds of Caesarean were not increased at 37/38 weeks, and reduced at 40/41 weeks (AOR 1.06 (0.96–1.18) at 37 weeks decreasing to 0.67 (0.65–0.70) at 41 weeks). Odds of postpartum haemorrhage and anal sphincter injury were also decreased, although neonatal admissions to special care baby unit were increased. In contrast, medically indicated IOL was associated with increased odds of perinatal mortality and increased maternal complication rates. Conclusion: These data suggest that complications of IOL relate to the indication rather than the process of IOL itself. Elective IOL at term is associated with decreased perinatal mortality, without an increase in Caesarean delivery.